Influence Of Motivation And Organizational Commitment On Work Satisfaction And Employee Performance - Ferum Mahendra Pranita (Proceedings of The ICECRS, 2017)
This study aims to determine the effect of motivation on job satisfaction between permanent employees and outsourcing in the period 2013-2015. Motivational influence on the performance of the jobholder and outsourcing. The influence of organizational commitment on job satisfaction among permanent employees and outsourcing. The influence of commitment organizational to employee performance between permanent employees and outsourcing by using SEM (Structural Equation Modeling). The effect of job satisfaction on employee performance. A sample of 60 respondents ie 55 permanent employees and five employees of outsourcing from year 2013 to 2015, then the authors examine the influence of motivation and organizational commitment to job satisfaction and employee performance, as for data collection techniques used by the researcher is a questionnaire is a technique of data collection in research by using a questionnaire that contains a list of questions to the respondent. Analytical techniques used in this study using Structural Equation Modeling (SEM) PLS operated by AMOS program 21.0. The results showed that there is a positive and significant influence between Motivation (X1) to Job Satisfaction (Y1), there is a positive and significant influence between Motivation (X1) on Performance (Y2), there is a positive and significant influence between Organizational Commitment (X2) on Job Satisfaction (Y1), exists a positive and significant influence between a positive and significant influence between Organizational Commitment (X2) to Performance (Y2), there is a positive and significant influence between Job Satisfaction (Y1) on Performance (Y2).